Pengaruh metode audio visual terhadap minat belajar dan hasil belajar Bahasa arab di Mts Negeri 2 Samarinda - Masdar, Ihsanuddin; khofifah, Erika nur (Borneo Journal of Language and Education, 2021)
This study aims to determine the effect of the audio-visual method on learning interest and learning outcomes of Arabic at MTs Negri 2 Samarinda.The type of research used in this research is a quantitative approach, The results showed that the audio-visual method influenced students' learning interest. It is known from the results of the research interest in learning Arabic through a questionnaire obtained a sig value (2-tailed = 0.000) < 0.025, and for the Arabic language test the post test value obtained a sig value (2-tailed = 0.000) < 0.025 ha is accepted and rejected so it is concluded there is a relationship/correlation between the audio-visual method and the interest in learning Arabic at MTs Negeri 2 Samarinda